SPECIFICS OF ECONOMIC TERMS IN THE UZBEK DICTIONARY - Yuldasheva Dilnoza Bekmurodovna; Raupov Jalil Shokirjonovich (Scholars Digest Publishing, 2023)
The article provides information about the uniqueness of economic terms in the Uzbek dictionary. This article is written about the features of the dictionary of the Uzbek language for the interpretation and understanding of economic terms. The article used such keywords as "economic term","dictionary", "concept", "characteristic" and "interpretation". The article describes how the dictionary of the Uzbek language can help to study and explain the meaning of terms used in economic fields.
Keywords: Economics, finance, business, investment, containment, inflation, additional tickets, import, investment.